Normal Pressure Hydrocephalus. Case Presentation - María Octavina Rodríguez Roque; Didiesdle Herrera Alonso; Ada Sánchez Lozano; Marines Herrera Rodríguez (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2017)
Normal Pressure Hydrocephalus, also known as Adult Chronic Hydrocephalus is usually produced in elder people due to an increase of cerebrospinal fluid in brain cavities, in general without an increase of intracranial pressure, but which can damage the brain. For such reasons, the case of a 67 year old mestizo, married patient is presented. She is an inveterate smoker who started suffering frequent falls without apparent cause, motor apraxia, sphincter disorders and perseverance. After consulting various specialties during a period of four years without diagnosis, she came to the Neurology consultation office reporting a deterioration of walking disturbances, sphincter disorders and very frequent falls. A research protocol was started due to the clinical suspect of normal pressure hydrocephalus which was confirmed by simple CT scan. It showed a dilation of the third ventricle without visualizing the fourth with effacement of convolutions and furrows. Through a Magnetic Resonance hydrocephalus was corroborated. She was admitted was medical and surgical treatment. An adequate valve was selected considering the hydrodynamic characteristics of the derivative system. Normal pressure hydrocephalus was corrected. This presentation is aimed at updating clinical diagnostic and therapeutic aspects of this gnoseological entity.